Anlysis of the European Union Allowances prices in the EU Emissions Trading Scheme 2008 — 2011 - Wen, yue (2012)
The European Union emission allowances (EUA) is a crucial element of the EU ETS which is the main policy instrument aimed at realizing the target of greenhouse gas emissions reduction of the European Commission’s Climate Change Program. This dissertation examines the key determinants of EUA pricing including energy prices, economic factors, hydroelectric consumption and CER prices based on the monthly prices of Phase II from 2008 — 2011. My study adopts regression models and statistic tests for analyzing these variables. The results suggest that the examined elements drive the changes of EUA prices and consistent variation trends with the time periods. The matter of financial crisis in 2008 was included in the consideration of the whole analyzing results.